Resistance to Patriarchy in Minangkabau Cinema - Vicia Dwi Prakarti DB; Dynia Fitri (LPPM Institut Seni Indonesia Padangpanjang, 2025)
This study examines forms of resistance to patriarchy in Minangkabau-themed cinema through an analysis of two films, Tenggelamnya Kapal Van der Wijck and Surau dan Silek. Although Minangkabau society is widely recognized for its matrilineal kinship system, social practices and cinematic representations continue to reflect strong patriarchal values, particularly in regulating gender relations, marriage, and female honor. This research employs a descriptive qualitative approach using film text analysis, visual observation, and literature review. The analysis is grounded in Stuart Hall’s theory of representation and feminist film theory, with particular attention to patriarchy and the concept of the male gaze. The findings indicate that women’s resistance in Minangkabau cinema is rarely portrayed in overt or confrontational forms; instead, it emerges through symbolic, emotional, and moral expressions embedded in narrative structures, characterization, and visual strategies. Women are represented as ethical subjects who negotiate their identities amid the pressures of tradition, religion, and modernity. Consequently, Minangkabau cinema functions as a cultural space that both reflects and critiques the paradox between matrilineal ideology and patriarchal practice within Minangkabau society.